Why Humanitarianism Needs a Pacifist Ethos. Issue 1 (2nd January 2020) - Moses, Jeremy
ABSTRACT: Debates concerning the relationship between humanitarianism and the use of force are by no means a new phenomenon, yet humanitarian rationales for waging war have become more and more commonplace over recent decades. The commitment to humanitarian intervention, in particular, raises deep theoretical and practical questions about the foundational principle of political neutrality espoused by many humanitarian aid organisations. In this paper I will provide an overview of the literature on the relationship between humanitarianism and the use of force before advancing the argument that a genuine humanitarianism must necessarily be premised upon a pacifist ethos. A pacifist ethos, in this context, is presented as a commitment to non-violence and anti-war activism even while recognising the limits of such an aspiration. Such an understanding of pacifism in practice, inspired in part by realist ethics, allows humanitarian actors to take strong, principled, and sustained stands in support of universal values of peace and human well-being without losing sight of the material challenges posed by the very real violence of the arenas in which they operate.